Assessing young learners' foreign language abilities. (January 2021) - Nikolov, Marianne; Timpe-Laughlin, Veronika
Abstract: Given the exponential growth in the popularity of early foreign language programs, coupled with an emphasis of evidence-based instruction, assessing young learners' (YLs) foreign language abilities has moved to center stage. This article canvasses how the field of assessing young learners of foreign languages has evolved over the past two decades. The review offers insights into how and why the field has developed, how constructs have been defined and operationalized, what language proficiency frameworks have been used, why children were assessed, what aspects of their foreign language proficiency have been assessed, who was involved in the assessment, and how the results have been used. By surveying trends in foreign language (FL) and content-based language learning programs involving children between the ages of 3 and 14, the article highlights research into assessment of and for learning, and critically discusses areas such as large-scale assessments and proficiency examinations, comparative and experimental studies, the impact of assessment, teachers' beliefs and assessment practices, young learners' test-taking strategies, age-appropriate tasks, alternative and technology-mediated assessment, as well as game-based assessments. The final section of the article highlights where more research is needed, thus outlining potential future directions for the field.